Ample textures for electromagnetic scattering in radiative transfer. (September 2020) - Mathew, T.; Rousseau, B.; Litman, A.; Favennec, Y.
Abstract: The numerical resolution of wave-matter interaction on complex micro heterogeneities constituting modern industrial materials poses significant computational hurdles. These computations hold a crucial role in the design cycle meant to optimize their participating behavior at high temperatures. To arrive at a reasonable conclusion at the expense of optimal resources, some textural details inherent to these materials are often truncated. For the accurate resolution of multi-scale thermal radiative transport, very little is known today about the role of these truncated textural information to the overall effective radiative properties. With the ultimate prospect of large scale finite element modeling of electromagnetic scattering for participating media, this initial attempt in 2D explores this aspect, learning from the ability of fractals to quantify textural details or roughness of complex objects. Based on a desirable error tolerance, critical quantitative limits were drawn, with which future large scale electromagnetic scattering computations can be performed confidently with optimum resources, without compromising the accuracy. From intensive numerical experiments, ample textural details relevant for a desired accuracy (1% error) of the extinction efficiency, scattering efficiency, and asymmetry parameter are quantified, and limits established. Error estimates for the aforementioned radiative properties at the limiting resolution (1 µm) of the economical imaging techniques today, are also drawn for better insights.